2016
DOI: 10.1111/bju.13607
|View full text |Cite
|
Sign up to set email alerts
|

Management of Radiation Therapy Oncology Group grade 4 urinary adverse events after radiotherapy for prostate cancer

Abstract: ObjectiveTo describe the management of Radiation Therapy Oncology Group (RTOG) grade 4 urinary adverse events (UAEs) after radiotherapy (RT) for prostate cancer (PCa). MethodsWe conducted a single-centre retrospective review, over a 6-year period (2010)(2011)(2012)(2013)(2014)(2015), to identify men with RTOG grade 4 UAEs after RT for PCa. RT was classified as combined therapy (radical prostatectomy [RP] followed by external beam radiotherapy [EBRT], EBRT + low-dose-rate [LDR] brachytherapy, EBRT + high-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
(48 reference statements)
2
2
0
Order By: Relevance
“…These findings are in keeping with data from Mayer et al. , who noted similarly that patients with complex radiotherapy complications required urinary diversion. Strictures were the next most common complication; ureteric strictures were more common than urethral.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in keeping with data from Mayer et al. , who noted similarly that patients with complex radiotherapy complications required urinary diversion. Strictures were the next most common complication; ureteric strictures were more common than urethral.…”
Section: Discussionsupporting
confidence: 91%
“…Frequently these complications required surgical intervention, and an operative rate of 67% was noted. Similar surgical intervention rates for patients with urinary adverse events after radiotherapy for prostate cancer have been reported .…”
Section: Discussionsupporting
confidence: 70%
“…From the study by Mayer et al, men who underwent UD were noted to have the most significant complications (nine in total) as well including three deaths, two Clavien-Dindo grade 4 complications and eight readmissions within 6 weeks of UD. The authors emphasize that UD is an option of last resort, as it is not without reported risk of complications (39%) and death (13%) [9].…”
Section: Complicationsmentioning
confidence: 92%
“…Mayer et al reported on urinary adverse sequelae of radiotherapy for treatment of prostate cancer [9]. In a retrospective review, they report the adverse urinary events of 73 men with prostate cancer treated with various radiation therapies.…”
Section: Indications For Urinary Diversionmentioning
confidence: 99%